An Evil to be Extinguished or a Resource to be harnessed-Informal Sector in Developing Countries: A Case of Zimbabwe - Sebele-Mpofu, Favourate Y; Moyo, Nomazulu (Journal of Economics and Behavioral Studies, 2021)
The informal sector remains a permanent feature of all economies. It is a more pronounced component of developing country economies where it is an integral part. Literature on economic development offers diverging viewpoints on the sector’s contribution to economic growth. On the one hand, researchers view the sector with positivity as a resource to be harnessed, capable of growth and innovation and on the other hand with negativity as a pure survivalist strategy and a stumbling block to effective policy formulation and economic development. Therefore as an inconvenience to be extinguished. The ambivalent view is further compounded by the sector’s paltry contribution to national tax revenues and as such, the IS has remained unappreciated and largely on the peripheral of economic reviews and policy responsiveness. The former view suggests that the latter is a misconception and narrow recognition of the sector as merely survivalist and contributing negligibly to employment creation and poverty alleviation efforts. Failure to recognize a coexistence of both street traders and firms with potential for growth, improved productivity and innovation, has consequently resulted in misguided policies. Policymakers pay little or no attention to the potential of informal sector firms, the challenges they face, the vulnerability they are exposed to and the appropriate support they require. This gap motivates this paper, as it seeks to explore the role played by the IS in developing countries with a special focus on Zimbabwe. The study employs a mixed-method research design. The research established that the sector remains unequivocally a major source of employment for many developing countries. It also established that a single-minded focus on formalizing the sector, linked to registration for tax purposes, ignores the other arm to the equation that is the creation of job opportunities, hospitable working conditions, improved productivity and increased profits which are possible with adequate policy support. The research recommends improved policy research and support which is development focused to aid informal firms to grow and be independent institutionally and financially from their owners as well as skills capacitation to improve operational and financial management.